Enhancing Operational Performance and Decision-Making through a Digital Data Tracking System - Seraspe, Jerald Ramos; Salamat, Franz; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The purpose of this study was to determine the effectiveness and im-pact of a digital office data tracking system in the performance and deci-sion-making of the selected employees. While manual tracking systems remain functional, their drawbacks, including inefficiency and potential for errors, make them less desirable compared to the modern and con-venient digital office tracking system. These reasons prompted the re-searcher to delve into the advantages and benefits this digital tracking system will provide the Department of Agrarian Reform. A survey research design was utilized to carry out this study. Find-ings indicate the majority of the fourteen (14) respondents were either satisfied or extremely satisfied with the current office data tracking sys-tem in place.